Comparative Photoelectric Performance Analysis of Key Semiconductor Materials for Optoelectronic Applications - Kirti Sharma,; Krishna Kumar Soni,; Vivek Kumar Jain, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study presents a comprehensive comparative analysis of the photoelectric properties of five semiconducting materials—Silicon (Si), Gallium Arsenide (GaAs), Cadmium Telluride (CdTe), Perovskites, and MoS2. The research evaluates their performance across parameters critical to photovoltaic and photodetector applications, including bandgap energy, absorption coefficient, carrier mobility, quantum efficiency, stability, and scalability. Data was analyzed through normalization, scoring matrices, and weighted performance indices. The study highlights the trade-offs between performance and practicality, with Silicon emerging as a reliable standard, Perovskites showing promise in efficiency, and GaAs dominating in specialized applications. Key limitations, such as material toxicity, cost, and environmental degradation, are discussed. The research supports informed selection of materials based on device-specific requirements and environmental sustainability.
Keywords: Photoelectric effect; semiconductor materials; photovoltaic efficiency; bandgap engineering; quantum efficiency; solar energy materials